2020
DOI: 10.1155/2020/9762015
|View full text |Cite
|
Sign up to set email alerts
|

What Is the Current Development Status of Wearable Device in Industrial 4.0? Using Technology Acceptance Model to Explore the Willingness and Pattern of Usage of the Consumers

Abstract: The object of the study is to use the technology acceptance model to explore the willingness and pattern of usage of the consumers. 205 valid questionnaires were collected by using the Google online survey platform. Using IBM SPSS and AMOS Statistics 20.0 software, first background information was analyzed, then CFA was used to analyze the relationship between variables, and SEM was used to verify the rationality of the measurement model. The result discovered that there is a positive effect on perceived usefu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…The player had a good perception of these five indexes, and the highest score was 4.10, which was involved in the ease to use and their attitude toward use. Liu et al ( 2020 ) applied the TAM to explore the willingness of consumers and use patterns by analyzing the background information, then exploring the relationship between variables, and verifying the reliability of the measurement model using search engine marketing (SEM). The results showed that the perceived utility of users had a positive impact on the usefulness of the product, their intention to use, their curiosity, and their willingness to use.…”
Section: Related Workmentioning
confidence: 99%
“…The player had a good perception of these five indexes, and the highest score was 4.10, which was involved in the ease to use and their attitude toward use. Liu et al ( 2020 ) applied the TAM to explore the willingness of consumers and use patterns by analyzing the background information, then exploring the relationship between variables, and verifying the reliability of the measurement model using search engine marketing (SEM). The results showed that the perceived utility of users had a positive impact on the usefulness of the product, their intention to use, their curiosity, and their willingness to use.…”
Section: Related Workmentioning
confidence: 99%